Does Universal Preschool Hit the Target? Program Access and Preschool Impacts - Elizabeth U. Cascio (Institute of Labor Economics (IZA), 2017)
Despite substantial interest in preschool as a means of narrowing the achievement gap, little is known about how particular program attributes might influence the achievement gains of disadvantaged preschoolers. This paper uses survey data on a recent cohort to explore the mediating influence of one key program attribute whether disadvantage itself is a criterion for preschool admission. Taking advantage of age-eligibility rules to construct an instrument for attendance, I find that universal state-funded prekindergarten (pre-K) programs generate substantial positive effects on the reading scores of low-income 4 year olds. State pre-K programs targeted toward disadvantaged children do not. Differences in other pre- K program requirements and population demographics cannot explain the larger positive impacts of universal programs. The alternatives to universal and targeted state pre-K programs also do not significantly differ. Together, these findings suggest that universal preschools offer a relatively high-quality learning experience for low-income children not reflected in typical quality metrics.
Keywords: H75; I24; I28; J13; J24; 330; early education; preschool; targeted; universal; access; quality